Evaluation of Adhesively-bonded Stiffeners by Numerical Modelling - Ferreira, J. A. M.; Campilho, R. D. S. G. (Technological Innovation in Engineering Research Vol. 3, 2022)
Large-scale implementation of a particular bonding process in any industry needs accurate tools for failure design and prediction. The performance of a structural adhesive (Araldite® 2015) on a T-stiffener with composite adherends made of an epoxy matrix reinforced with carbon fibres is investigated in this study. The aim of the work is to numerically study, by the Finite Element Method (FEM) and Cohesive Zone Models (CZM), the behaviour of different T-stiffener bonded with a structural epoxy adhesive when subjected to peel loads and different geometries. A parametric study was carried out, considering an elastic stress analysis and maximum load (Pm) prediction based on CZM modelling, considering the variation of four geometrical parameters: flat adherend thickness (tP), stiffener thickness (t0), overlap length (LO) and curved deltoid radius (R), to achieve the optimal configuration. All tested parameters had a substantial effect on both stress distributions and Pm, allowing the optimal joint parameters for T-stiffeners to be determined.